Design and Construction of the Real Felipe Fortress of Callao: Analysis of the Military Treatise and Layout Using Photogrammetry and GIS - Diego Javier Celis-Estrada; Pablo Rodriguez-Navarro; Teresa Gil-Piqueras (Heritage)
Peru constituted the most important Viceroyalty of the Spanish Empire in South America, with the Port of Callao controlling the South Pacific trade routes. Although it was safe in its infancy, Callao suffered coastal attacks leading to its fortification. However, on 28 October 1746, an earthquake and tidal wave devastated the port, leading to its relocation and the construction of the Real Felipe Fortress of Callao, the South Pacific’s most significant fortification. The fortress was based on 18th century military conceptions adapted to the specific conditions of the coastal lands of the Peruvian Viceroyalty, such as the lack of stone, the use of adobe, and the frequent earthquakes. This research sought to identify the architectural theories influencing its design, the adaptations necessary for its coastal location, and the underlying mathematical and military concepts. Photogrammetry based techniques and a geographic information system (GIS) were used for georeferencing historical planimetry, along with the analysis of historical documents. This allowed us to reconstruct the original design and make evident how European ideas were adjusted to the particularities of the American territory, thus contributing to the improvement of knowledge about Spanish military architecture in America.